9,10-Dimethyl-9,10-peroxy-9,10-dihydroanthracene - Wang, Yun-Wu (International Union of Crystallography, 2008)
The structure of the title compound, C(16)H(14)O(2), contains one half-molecule in the asymmetric unit and the molecule is located on a mirror plane. The dihedral angle between the two benzene ring planes is 53.07 (6)°. The crystal structure involves intermolecular C—H⋯O hydrogen bonds.